Recent Advances and Future Prospects of Phthalimide Derivatives - Neelottama Kushwaha,Darpan Kaushik (Journal of Applied Pharmaceutical Science, 2016)
Among bicyclic non-aromatic nitrogen heterocycles, phthalimides are an interesting class of compounds with a large range of applications. Phthalimide contains an imide functional group and may be considered as nitrogen analogues of anhydrides or as diacyl derivatives of ammonia. They are lipophilic and neutral compounds and can therefore easily cross biological membranes in vivo and showing different pharmacological activities. In the present work compounds containing phthalimide subunit have been described as a scaffold to design new prototypes drug candidates with different biological activities and are used in different diseases as, for example AIDS, tumor, diabetes, multiple myeloma, convulsion, inflammation, pain, bacterial infection among others.
Keywords: Phthalimide derivatives,imide,biological activity.